An Empirical Study on Integration of Experiential Learning and Mobile Learning - Leung , Chi Hong; Cheng, Simone Chung Ling (Asian Journal of Empirical Research, 2019)
This paper discusses how experiential learning and mobile learning can be integrated to facilitate knowledge acquisition and knowledge sharing among students, and equip students with the abilities to solve real-world problems in a ubiquitous manner. Running in a cyclic manner, experiential learning guides students to interpret why something happened, plan what should be done in the future, collect and manipulate facts and data, and experience and reveal what they learnt. With the capabilities of current mobile devices (like virtual personal assistants), experiential learning can be implemented with a higher level of effectiveness. The results reveal that experiential learning is beneficial for learners who believe it can help them to solve practical problems and the usage of mobile devices can offer flexibility to study and address the diversity of learners’ needs.